Fetal outcome of HIV positive pregnant women taking highly active antiretroviral therapy at Yaoundé Central Hospital: a cross sectional analytic study - J. H., Fouedjio; Ntani, Loweh Limyuy; Florent, Fouelifack Ymélé; Mbu Robinson Enow, Mbu Robinson (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: HIV infection in pregnant women is delicate both for the mother and her child. With the adoption of option B+ treatment plan by Cameroon’s ministry of public health, there has been a marked decrease in the vertical transmission of HIV from mothers to their babies. There is a dearth of evidence in sub-Saharan Africa, especially in Cameroon, on the effects of highly active antiretroviral therapy (HAART) on pregnancy and foetal outcomes with respect to the time from onset of treatment. We therefore carried out this study to determine the foetal outcome of women on HAART. We hypothesized that the foetal outcome is poorer for pregnant women starting HAART during pregnancy compared to those starting HAART prior to conception. Methods: We carried out an analytic cross-sectional study which spanned from the 1st February to 30th April 2017 at the Yaoundé Central Maternity. We included consenting hospitalised HIV infected women who just terminated a pregnancy (abortion or delivery), and who started HAART at least four weeks before termination of pregnancy. Data was analysed using EPI info 7.2.1.0. SPSS version 20.0. Odds ratio (OR) was used to assess the degree of association that could exist between qualitative variables. The threshold of statistical significance was set at a p-value of 0.05. Results: A total of 121 participants were recruited in the present study. The mean age of the participants was 31.3±5.3 years for those who started HAART before pregnancy and 29.4±5.5 years for those who started during pregnancy (p=0.07). The viral loads means for those who started taking HAART before pregnancy 34.6±21.5 cells/mm3 and those who started during pregnancy 60±14 cells/mm3 (p = 0.01). Overall there were not any significant adverse fetal outcomes caused by taking HAART before or during pregnancy (p >0.05). Conclusions: Despite the fact that the viral load was more elevated in women starting HAART prior pregnancy compared to those started during pregnancy, there was no significant adverse foetal outcome related to time of initiation of HAART treatment by pregnant HIV positive in Yaoundé central Maternity. We suggest that the implementing of the test and treat strategy will have a positive impact on the vertical transmission of HIV.